Formability of tailor welded blanks of aluminium alloy and steel – A review. (2021) - Deepika, D.; Anitha Lakshmi, A.; Srinivasa Rao, Ch.; Sateesh, N.; Nookaraju, B. Ch.; Subbiah, Ram
Abstract: Aluminum alloys are primarily focused on shipbuilding and aerospace industries due to its special characteristics and low cost, good durability and extreme service conditions. Steel has focused on infrastructure, ships due to its little cost and high tensile strength. The present work studies the formability performance of tailor welded blanks of aluminium alloy and steel materials used in the aerospace and automotive industries.